THE PATHS OF FEMALE EDUCATION - Almeida, Antônia Rosa; Rodrigues, João Bartolomeu; Silva, Levi Leonido Fernandes da; Morgado, Elsa Maria Gabriel (Cadernos de Educação Tecnologia e Sociedade, 2020)
Since man is a man, history has been responsible for showing the progress of life in society and, analyzing the foundations of education, one can understand the advances and setbacks in the segments that support it. One must remember the importance and meaning of education to realize itâ€s contribution to people in particular and to humanity in general. For women, education is a great example of building for citizenship. Female empowerment and its entire universe overlap with the history of education, with the infinite property through the consolidation of social struggles and female resistance to what was imposed by society. The march of women made the role of education multiply in the face of more varied realities, whether in the rural environment or in the urban environment, in the most different spaces. It is known that the motivation for the search for knowledge in the circumstances in which women lived in the past was decisive for being the provocateur of women's empowerment, because it is a right for all, in the journey of the whole social force, family, religion, politics, culture, and work. In what was proposed by the advent of the role in the life of women, it is perceived that the force linked to power, wanting to learn have become more accessible to women and this development throughout life marks the vicissitudes that education manifested in the life of each individual.